Caracterização de genótipos de alface e estimativas de parâmetros genéticos para pigmentos foliares - Vieira, Joana D'arc Mendes (2020)
Lettuce (Lactuca sativa L.) is the most consumed leafy vegetable in the world. The insertion of this vegetable in the diet brings important health benefits, especially due to the complex mixture of bioactive compounds in its leaves, such as carotenoids, anthocyanins and chlorophyll. The increase in the levels of these phytochemicals in lettuce can increase their intake, without necessarily requiring an increase in consumption. In the genetic improvement of lettuce it is important to obtain genotypes that add a series of favorable characters, both related to its function as a functional food, and in the agronomic scope. Thus, the objectives in this work were to evaluate the levels of anthocyanins, carotenoids and chlorophyll in leaves of lettuce plants, correlating them with colorimetric and color scale characters, as well as characterizing progenies in order to identify appropriate genotypes for the market. To obtain the plants of the generations of the object of the study, a cross was made between the contrasting cultivars for leaf type, Red Star (red color, of curly and loose leaves) and Darkland (dark green color of the Roman type) and the necessary self-foundations. Then, an experiment was conducted in which 36 plants from each parent and F1 generation were used, 312 plants from generation F2 and 36 plants from each of the 30 F2:3 progenies obtained. Plants of the different genotypes were distributed in beds, following the complete randomized block design, with three replications. When the plants reached commercial maturity, they were evaluated for the following characters: total anthocyanin content, total carotenoid content; chlorophyll content index SPAD; colorimetric coordinates L*, a*, b*, chroma and ºhue; besides a scale of notes for type of limbo, type of border, commercial type and color of the leaves. The plants of each of the progenies, due to the high number of plants, were evaluated only for the characteristics based on scale of notes, while the other populations were evaluated for all the characters. The data collected through evaluations on the parents and the F1 and F2 populations were used to estimate genetic parameters, in order to determine the type of genetic control involved in the expression of the characters. The population means were used to perform a correlation analysis between the characters. In relation to the progenies, the comparison of means was performed by the Dunnett test, at 5% probability, between each F2:3 progeny and each of the parents, in order to confirm the type of segregation. It was found that there was predominantly partial dominance gene action for all characters related to the color of the lettuce leaf. The red color can be used as an aid in lettuce breeding programs for the selection of genotypes with a high content of anthocyanins and carotenoids. The use of colorimetry and scale of leaf color notes can be used as effective methods to infer on the content of anthocyanins and carotenoids and chlorophyll index, due to the strong correlations between these characters. There was a high heritability in the broad sense, around 90% for most characters, which in turn, can favor gains with phenotypic selection. Although most of the F2:3 progenies still present segregation for agronomic traits, the UFLA34 progeny showed minimal variation in these characters, and may be already more homozygous.